Assessing climate change impacts on water resources in the Ganges-Brahmaputra-Meghna river basin - Khandu (Curtin University, 2016)
With a population of over 650 million, the water resources in the Ganges - Brahmaputra - Meghna (GBM) River Basin are under enormous pressure from both climate change and increasing demands from a rapidly growing population. This thesis provides an improved understanding of the combined impacts of climate change and human water abstraction on the basin's available freshwater storage, through a combination of in-situ and satellite-based observations, state-of-the-art regional climate modelling, and hydrological modelling approaches.